Deformable concrete for earthquake-proof buildings. (Research'eu results magazine)
When creating structures capable of withstanding earthquakes, engineers currently rely on force-based methods only. They cannot decide how the structure will adapt to seismic vibrations, which can in turn lead to undesirable failures. An innovative design for a highly deformable reinforced concrete structure is hoped to bring such freedom, whilst optimising the use of resources, minimising costs and ensuring safety.